Mutual Legal Assistance International Agreement in Eradicating Transnational Crime - Andika Jinaratana; Yofi Permatasari; Jean Claudia (Asian Journal of Social and Humanities, 2023)
Transnational crime can be said to be one of the threats that has quite a big impact on Indonesia's security. So that there are no more obstacles in eradicating transnational crime, cooperation between countries is needed through Mutual Legal Assistance (MLA) agreements. The application of mutual legal assistance is implemented to increase the effectiveness of cooperation in eradicating transnational crimes. The existence of an international Mutual Legal Assistance agreement that functions to carry out cooperation between countries, which includes investigations and examinations at trials until the implementation of court decisions, can complement the enforcement of extradition agreements